Accommodative 101̅2 twins at high angle grain boundaries in rolled pure titanium. (15th April 2016) - Xu, Shun; Schuman, Christophe; Lecomte, Jean-Sébastien
Abstract: The intersection of two 10 1 ̅ 2 twins has been extensively reported in hexagonal metals and appears at grain boundaries with low misorientation angles. In the current work, compression was applied along the normal direction of rolled pure titanium. Primary 11 2 ̅ 2 contraction twins accommodated by adjacent 10 1 ̅ 2 extension twins were found at high angle grain boundaries with misorientation angles close to 90°. The mechanism accounting for the variant selection of the adjoined 10 1 ̅ 2 twins is examined in terms of Schmid factor and accommodation capacity of potential twin variants. Graphical abstract: Discovery of a {10–12} twin accommodating the strain induced by a {11–22} twin at high angle grain boundaries